Proceedings of the 12th EAI International Conference on Mobile and Ubiquitous Systems: Computing, Networking and Services 2015
DOI: 10.4108/eai.22-7-2015.2260306
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Detecting Damage of Traffic Marks by Half Celestial Camera Attached to Cars

Abstract: Roads are becoming deterioration in everywhere. In some places, traffic marks painted on roads are damaged thus needed to be updated. Municipalities must manage road condition and traffic marks (road painting). It is the municipalities task to manage those roads using, for example, special inspection cars and human eyes. However, the management cost is high if a city contains many roads. This paper proposes a mechanism that automates this management. Our idea is to leverage cameras attached to garbage trucks, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The overall model performance is obtained via averaging predictive outcomes of the 5 data folds. This process has been proved to be a robust method for model hyperparameter selection [49]. Notably, in each generation, based on the computed cost function, the location of population members is updated and the stopping criterion is checked to verify whether the current generation number exceeds the allowable value.…”
Section: Methodsmentioning
confidence: 99%
“…The overall model performance is obtained via averaging predictive outcomes of the 5 data folds. This process has been proved to be a robust method for model hyperparameter selection [49]. Notably, in each generation, based on the computed cost function, the location of population members is updated and the stopping criterion is checked to verify whether the current generation number exceeds the allowable value.…”
Section: Methodsmentioning
confidence: 99%
“…In [52], the authors presented an algorithm that identified damage to road markings. To ensure privacy, the algorithm was implemented using a half-celestial camera positioned on the underside of a vehicle, specifically a rubbish lorry.…”
Section: Related Workmentioning
confidence: 99%